Sports Sellers’ Psychological Capacity Effect on Sales Amount and Client Satisfaction - Hassan Gharehkhani; Behzad Izadi; Ziba Nasiri (Sports Business Journal, 2022)
Purpose: This study aimed to evaluate the effect of the psychological capacity of sports sellers on sales amount and client satisfaction mediated by Client-centred behavior.Methodology: The research was applied correlational. Iranian leading sports sellers were selected as a sample. Data were collected using the Lussier and Hartmann (2017) questionnaire (reliability 0.7). The PLS Smart software was used to analyse the data.Findings: The highest correlation was observed between the variables of psychological capacities and customer-oriented behavior (0.835). The lowest correlation was between customer satisfaction and sales performance (0.211). There was a positive and significant relationship (0.79) between psychological capacities and the seller’s client-centered behaviors. Client-oriented behavior effect of sports sellers on sales amount (0.78) and client satisfaction (0.65) was also positive and significant.Originality: Considering the impact of sports sellers’ customer-oriented behavior on sales and customer satisfaction, it is recommended that sports sellers pay special attention to learning and applying customer-oriented behaviors.